KOMPOZİT YARI İLETKEN FOTOANOTLARIN BOYA DUYARLI HİBRİT GÜNEŞ PİLİ PERFORMANSINA ETKİSİ - DEMİR, ABDULLAH (Fırat Üniveristesi, 2022)
Bu tez çalışmasında, hidrotermal yöntemi ile üretilen TiO2 ve ZnO tozlarının boya duyarlı güneş pillerinin (BDGP) performansını nasıl etkilediği araştırılmıştır. Üretilen tozlardan, saf TiO2, ağırlıkça 3:1 TiO2/ZnO, 1:1 TiO2/ZnO, 1:3 TiO2/ZnO ve saf ZnO olmak üzere 5 farklı boya duyarlı hibrit güneş pili üretilmiştir. İletken cam olarak florin katkılı kalay oksit (FTO), karşıt elektrot olarak platin (Pt) ve boya olarak rutenyum (Ru) tercih edilmiştir. FTO üzerine farklı oranlardaki ZnO:TiO2 fotoanotları serigrafi yöntemi ile kaplanmıştır. Üretilen fotoanotların morfolojik ve minerolojik analizleri SEM, XRD ve EDX ile belirlenmiştir. XRD analizleri ise hedeflenen kristal fazlarının yapıda oluştuğunu doğrulamıştır. TiO2 ve ZnO taneciklerinin morfolojisi incelendiğinde taneciklerin sıkıca paketlendiklerini ve TiO2 miktarı arttıkça daha pürüzsüz bir yapı oluştuğu SEM görüntüleri ile gözlemlenmiştir. Üretilen boya duyarlı güneş pillerinin fotovoltaik parametreleri solar simülatör cihazı ile analiz edilmiştir. TiO2:ZnO oranı değiştikçe pil verimlerinin (% 0,0013-2,3613 aralığında) değiştiği saptanmıştır. En yüksek verimi (?) saf TiO2 fotoanoduna sahip boya duyarlı güneş pilinin sergilediği gözlemlenmiş ve TiO2 oranı arttıkça pil verimlerinde bariz bir artış olduğu tespit edilmiştir. Oransal olarak TiO2 miktarı artıkça verimin yükselmesi TiO2'nin daha kararlı bir yapıya sahip olduğunu göstermiştir.

In this thesis, it was investigated how TiO2 and ZnO powders produced by hydrothermal method affect the performance of dye-sensitized solar cells. From the produced powders, 5 different dye-sensitive hybrid solar cells by weight were produced as Pure TiO2, 3:1 TiO2/ZnO, 1:1 TiO2/ZnO, 1:3 TiO2/ZnO and pure ZnO. Fluorine-doped tin oxide (FTO) was preferred as the conductive glass, platinum (Pt) as the counter electrode, and ruthenium (Ru) as the dye. ZnO:TiO2 photoanodes in different ratios were coated on the FTO by screen printing method. Morphological and mineralogical analyzes of the produced photoanodes were determined by SEM, XRD and EDX. XRD analyzes confirmed that the targeted crystal phases were formed in the structure. When the morphology of TiO2 and ZnO particles was examined, it was observed with SEM images that the particles were tightly packed and a smoother structure was formed as the amount of TiO2 increased. The photovoltaic parameters of the produced dye-sensitized solar cells were analyzed with a solar simulator device. It was determined that as the TiO2:ZnO ratio changes, the solar cell efficiencies (in the range of 0.0013-2.3613) change. It was observed that the dye-sensitized solar cell with pure TiO2 photoanode exhibited the highest efficiency (?), and it was determined that there was a clear increase in cell efficiency as the TiO2 ratio increased. The increase in efficiency as the amount of TiO2 increases proportionally showed that TiO2 has a more stable structure.
Effect of composite semi-conductor photoanodes on dye-sensitive hybrid solar cell performance
Keywords: Enerji